2017
DOI: 10.1186/s12984-017-0341-z
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive measurement of stroke gait characteristics with a single accelerometer in the laboratory and community: a feasibility, validity and reliability study

Abstract: BackgroundApplication of objective measurement of stroke gait with accelerometer-based wearable technology and associated algorithms is increasing, despite reports questioning the accuracy of this technique in quantifying specific stroke-related gait impairments. The aim of this study is to determine the feasibility, validity and reliability of a low-cost open-source system incorporating algorithms and a single tri-axial accelerometer-based wearable to quantify gait characteristics in the laboratory and commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 42 publications
3
47
0
Order By: Relevance
“…All of them evaluated gait-related outcomes, but they differed considerably in the chosen setting. Two studies assessed the usability of a sensor system by reporting inconvenience [ 26 ] and adverse events [ 27 ], respectively, while eight studies reported the wearing time of the sensors in daily life [ 28 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them evaluated gait-related outcomes, but they differed considerably in the chosen setting. Two studies assessed the usability of a sensor system by reporting inconvenience [ 26 ] and adverse events [ 27 ], respectively, while eight studies reported the wearing time of the sensors in daily life [ 28 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This in turn enables the estimation of step frequency and cadence. Walking bouts were further analyzed in terms of temporo-spatial gait parameters [ 27 , 28 , 33 , 40 , 58 , 61 , 70 , 81 , 82 , 86 , 91 , 93 ], and joint kinematics (i.e. knee angle) [ 33 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Hemiplegia is one of the most common impairments after stroke and significantly reduces walking ability. Poststroke hemiplegic gait is typically characterized by a reduced gait velocity and asymmetry of bilateral kinetic, kinematic and spatiotemporal parameters [ 1 3 ]. Gait function is an important factor in determining the ability to independently perform activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…Hemiplegia is one of the most common impairments after stroke and signi cantly reduces walking ability. Poststroke hemiplegic gait is typically characterized by a reduced gait velocity and asymmetry of bilateral kinetic, kinematic and spatiotemporal parameters [1][2][3]. Gait function is an important factor in determining the ability to independently perform activities of daily living.…”
Section: Introductionmentioning
confidence: 99%